HOW FINANCIAL INFORMATION AFFECTS DIVIDEND POLICY TO ENCOURAGE THE INDONESIAN ECONOMIC SECTOR IN POST COVID-19 PANDEMIC - Deitiana, Tita; Pusvikasari, Nila; Arilyn, Erika Jimena; Beny , Beny (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence about the factors that influence dividend policy to encourage the post-Covid-19 pandemic Indonesian economic sector. The independent variables in this study are financial information which consists of company size, leverage, risk, free cash flow, diversification loss, earning volatility, and managerial ownership. This research is a quantitative explanatory approach using correlational design through Partial Least Square (PLS). Thirty out of forty-five liquid companies (LQ-45) listed in Indonesia Stock Exchange (IDX) were gathered especially before and during the pandemic from 2013 until 2020 with the following criteria: The firms that are listed on the Stock Exchange of Indonesia during the years 2013 until 2020 and financial statement data are available for the period of the study. These results show that risk and leverage have a negative impact on dividend policy, but other factors which are free cash flow, size of the company, loss from diversification, volatility of earnings, and managerial ownership had no impact on it.